Optimization of chitosan and sodium tripolyphosphate as a carrier system for nanoparticles of ethanol extract of aloe vera (Aloe vera l.) as an antioxidant - Efrilia, Erin; Sunarni, Titik; Kuncahyo, Ilham (Surya Hijau Manfaat, 2025)
Aloe Vera has phenolic active compounds that are proven to have potential antioxidant activity but are sensitive to light, easily oxidized and unstable at high temperatures. To overcome this, aloe vera is formulated into a chitosan and sodium tripolyphosphate carrier system. The interaction between chitosan and sodium tripolyphosphate for nanoparticle formation is strongly influenced by the ratio of both. The purpose of this study was to obtain the optimal formula of aloe vera extract nanoparticle preparation with chitosan and sodium tripolyphosphate carrier system with critical parameters including particle size, polydispersity index, zeta potential, sorption efficiency and antioxidant activity. Aloe vera was extracted with 96% ethanol using maceration method. Determination of chitosan and sodium tripolyphosphate concentration variation using simplex lattice design method. The results of the tests that have been carried out, the characteristics of aloe vera nanoparticle preparations with variations in the concentration of chitosan: sodium tripolyphosphate in runs 2 & 6 have the most optimal formula with the ratio of chitosan: sodium tripolyphosphate = (0.3: 0.1).